Odpowiedzi

2010-02-22T19:46:32+01:00
A)=8a-4+2a-5+3a-1=13a-9
13×5-9=65-9=56
b)=8x-4y+14x+6y+12x+12y=34x+14y
34×(-0,5)+14×0,5=-17+7=-10
2010-02-22T19:54:13+01:00
A) -4*((-2)*(-5)+1)-((-2)*(-5)+5)+(3*(-5)-1)= -4*11-15+(-16)=44-15+(-16)=29+(-16)=13
b) 4*(2*(-0.5)-0.5)+2*(7*(-0.5)+3*0.5)-12*((-0.5)-0.5)=4*0.5+2*(-2)-12*(-1)=2+4-(-12)=6-(-12)=6+12=18

2010-02-22T19:59:28+01:00
A) -4(-2a+1)-(-2a+5)+(3a-1)
8a-4+2a-5+3a-1
8*(-5)-4+2*(-5)-5+3*(-5)-1
-40-4+(-10)-5+(-15)-1
-40-4-10-5-15-1=-75

b)4(2x-y)+2(7x+3y)-12(-x-y)
8x-4y+14x+6y-12x+12y
8*(-0,5)-4*0,5+14*(-0,5)+6*0,5-12*(-0,5)+12*0,5
-4-2-7+3+6+6=2